2017
DOI: 10.1093/jxb/erx349
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of a starch phenotype from wild wheat to bread wheat by deletion of a locus controlling B-type starch granule content

Abstract: We describe the production and characterization of bread wheat with grains that lack small B-type starch granules, have near-normal weight and starch content, and have novel grain and starch physicochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…The mutant was found to have few, if any B-granules, like Ae. peregrina and a hexaploid bread wheat (Paragon) double-mutant with deletions of the BGC1-regions of chromosomes 4A and 4D (Chia et al, 2017). This result confirms that BGC1 is an ortholog of FLO6 and shows that FLO6 controls B-granule content in wheat and Aegilops.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The mutant was found to have few, if any B-granules, like Ae. peregrina and a hexaploid bread wheat (Paragon) double-mutant with deletions of the BGC1-regions of chromosomes 4A and 4D (Chia et al, 2017). This result confirms that BGC1 is an ortholog of FLO6 and shows that FLO6 controls B-granule content in wheat and Aegilops.…”
Section: Discussionsupporting
confidence: 66%
“…We used the Aegilops genetic map to establish the syntenic interval in the reference hexaploid bread wheat genome of accession Chinese Spring. Our previous analysis of bread wheat deletion mutants showed that BGC1 is present in at least two genomes (A and D; Chia et al, 2017). We therefore simplified the synteny analysis by ignoring genes in the region of interest that are present in only one genome ( Fig.…”
Section: Floury Endosperm 6 Is a Strong Candidate For Bgc1mentioning
confidence: 99%
See 2 more Smart Citations
“…QTL mapping studies in the wild wheat Aegilops peregrina identified a gene locus, termed Bgc-1 that is located on the short arm of chromosome 4S, which appears to control the initiation or synthesis of B-granules [418]. Recent deletion studies in bread wheat detected orthologous Bgc-1 regions, which, when deleted, result in the loss of B-granules in the endosperm, but interestingly, no yield penalty [419]. The SS isoforms involved in granule initiation (SSIII and SSIV, see above) clearly play a role in determining granule size and number, but other proteins are likely to be involved.…”
Section: Starch Granule Growth Size and Morphologymentioning
confidence: 99%